Mixed treatment comparison of efficacy and tolerability of biologic agents in patients with rheumatoid arthritis. (October 2013) - Hochberg, Marc C.; Berry, Scott; Broglio, Kristine; Rosenblatt, Lisa; Nadkarni, Anagha; Trivedi, Digisha; Hebden, Tony
Abstract Objective: To determine the comparative efficacy and tolerability of abatacept and tumor necrosis factor inhibitors (TNFi) in patients with rheumatoid arthritis (RA) and inadequate response to conventional disease modifying anti-rheumatic drugs (DMARDs). Research design and methods: A systematic review identified RCTs in RA patients who responded inadequately to conventional DMARDs and were treated with one of the following biologic agents: abatacept, adalimumab, etanercept, infliximab, certolizumab pegol, or golimumab. Bayesian hierarchical models were used to compare efficacy and tolerability outcomes of abatacept and combined TNFi at 6 months and 1 year. Results: In this mixed treatment comparison (MTC), the likelihood of achieving ACR response was comparable between abatacept and combined TNFi at 6 months for ACR20, 50, and 70: (odds ratio [OR] = 0.98 [95% confidence interval (CI): 0.73, 1.27], 0.99 [0.73, 1.31], and 0.91 [0.62, 1.27], respectively); and at 12 months for ACR20 (OR = 1.27 [0.92, 1.71]) and ACR50 (1.21 [0.82, 1.68]), with a higher likelihood of achieving an ACR70 response at 12 months (1.41 [1.02, 1.82]). Odds of DAS28 remission at 12 months was greater for abatacept than the combined TNFi (OR = 2.03 [1.04, 3.58]). Abatacept had better tolerability, defined as a lower likelihood of withdrawal due to adverse events, at both 6 and 12 months (OR = 0.38 [0.10, 0.88] and 0.51 [0.27, 0.86], respectively). These analyses include indirect comparisons across clinical trials and are not a replacement for head-to-head data. While all TNFi have been grouped into one class, there may be some differences between the individual TNFi that are not captured in our study. Conclusions: In this MTC, abatacept demonstrated similar efficacy at 6 months, a higher likelihood of achieving ACR70 response and DAS28 remission at 12 months and better tolerability relative to the combined TNFi in patients with RA who had an inadequate response to conventional DMARDs.